2017
DOI: 10.1093/cid/cix902
|View full text |Cite
|
Sign up to set email alerts
|

High Human Immunodeficiency Virus Incidence and Prevalence and Associated Factors Among Adolescent Sexual Minority Males—3 Cities, 2015

Abstract: HIV-related risk behaviors, prevalence, and estimated incidence density for adolescent SMM were high, especially for minority SMM. Our findings suggest that initiating intervention efforts early may be helpful in combating these trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…Details on sampling and recruitment methods have been published previously. 4 Participation in NHBS-YMSM was anonymous. A waiver of documentation of informed consent was requested and received for all three study sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on sampling and recruitment methods have been published previously. 4 Participation in NHBS-YMSM was anonymous. A waiver of documentation of informed consent was requested and received for all three study sites.…”
Section: Methodsmentioning
confidence: 99%
“…Research indicates that adolescent MSM are more likely to engage in risky sexual behaviors compared to their heterosexual counterparts. 4,5 The 2017 National Youth Risk Behavior Survey found that adolescent MSM were more likely than those who had sexual contact with only females to have sexual intercourse before age 13 years and inject illegal drugs and less likely to have used a condom at last sex. 5 These behaviors are paired with the reality that adolescents as a whole are less likely to access and use quality prevention and clinical services.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Specifically, SGMY are at high risk of experiencing mental health disparities while also being at disproportionate risk for sexually transmitted infections (STIs) and HIV. [6][7][8][9] This study describes the availability of sexual health, STI, and HIV services by publicly funded mental health programs that serve SGMY in Southern California, a highly diverse region. SGMY are significantly more likely to experience conditions that can elevate the likelihood of mental and physical health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma and discrimination by family, peers, and community members due to youth's gender and sexual orientation contribute to adverse mental health outcomes among SGMY, [10][11][12][13] including higher rates of suicidality, depression, and anxiety disorders. 12,[14][15][16] SGMY experience higher rates of STIs and HIV than heterosexual/cisgender youth, [6][7][8][9] in part because of engagement in risky sexual behaviors (e.g., infrequent condom use, multiple sexual partners, and trading sex) and higher rates of alcohol and illicit drug use-potentially as coping mechanism, which may subsequently contribute to unsafe sexual practices. [17][18][19][20][21][22][23][24] Importantly, systematic discrimination, such as bullying and physical and sexual abuse, including forced sex or sexual dating violence, has resulted in the overrepresentation of SGMY among homeless or housing insecure youth.…”
Section: Introductionmentioning
confidence: 99%
“…Those individuals testing negative can engage in interventions to prevent HIV acquisition, such as behavioral counseling and PrEP initiation. Due to the high HIV incidence among YMSM, routine HIV testing is particularly important and represents an ongoing prevention activity that requires strategies for continued engagement [ 12 ]. Access to and uptake of HIV testing is suboptimal, even among YMSM who report behaviors that place them at high risk for infection [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%